Use of captagon in a case with asperger syndrome - Kardaş, Ömer; Balça Çapan, Yeliz; Yüksel, Mehmet Emin; Tunca, Hüseyin (Journal of Dependence, 2019)
Asperger syndrome is a disorder defined by social and emotional restrictions and associated with repetitive behaviour and interests. Asperger syndrome signs begin in childhood and It persists lifelong. Alcohol abuse has been reported as 7% percent in Asperger syndrome cases while alcohol and substance abuse has been reported as 16% percent for the adults with the autism spectrum disorder. Captagon is an amphetamine derivative and its main ingredient is fenethylline. It is chemically formed by combining amphetamine and theophylline. In the literature, also known as psychoterorizan, captagon has been reported to have effects such as fearlessness, euphoria, forcefulness, keeping awake for days, killing without any consideration after used among terrorist groups. Our case who used captagon at age 16 first, had an increase in the amount of energy and according to the statement of the family after using the substance, he had walked about 90 km from one district to another and talked about to have special powers, such as resurrecting the deads with the ring on his finger which are clear signs of a psychotic. In this study, it is aimed to report on the usage and effects of Captagon that is a rarely known substance by a adolescent with Asperger syndrome.
Keywords: Asperger syndrome; captagon; autism spectrum disorder; adolescent